DIRETRIZES DO MELHORAMENTO DAS RAÃ‡AS BOVINAS E ZEBUINAS CRIADAS NO BRASIL - Domingues, Octavio (REVISTA DE AGRICULTURA, 2016)
DIRETRIZES DO MELHORAMENTO DAS RAÃ‡AS BOVINAS E ZEBUINAS CRIADAS NO BRASIL